HPAM : hybrid protocol for application layer multicast - Yeo, Chai Kiat (2008)
This dissertation presents Hybrid Protocol for Application Layer Multicast (HPAM) which is used to stream live media over the Internet without IP multicast support. HPAM self-organizes clients to form efficient, self-improving, self-repairing, source-based overlay trees which minimize the root latency as well as loss rate for each client. HPAM exploits the simplicity and optimality of a lightweight, centralized controller, DS (Directory Server), with the robustness and scaleability of distributed clients. DS facilitates peer discovery and serves as a reliable backup should the distributed algorithm fails. Tree construction, refinement and recovery from partitions are executed independently by the clients. Other innovations of HPAM include: the JoinSource&Adopt algorithm to specially minimize the latency of clients located right below the root; the Gossip and Spiral mechanisms for tree refinement and repair; the Relative Loss Rate based heuristics for the detection of possible local congestion between a client and its parent to reduce unnecessary parent switching; the study on the impact of cheating clients who fabricate distance measurements on HPAM’s performance; the cheat detection techniques. In essence, it can build and maintain application layer multicast trees with reasonable overheads and network stress and is able to deliver high QoS to its clients.